Desenvolvimento de Plutella xylostella (Linnaeus, 1758) (Lepidoptera: Plutellidae) em Brassicaceae ao longo de gerações - Dibelli, Wanderlei [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Species of Brassicaceae family are part of the global food base. Nutritional characteristics of brassics show high levels of vitamins, fiber, minerals, phenols, flavonoids, hydroxycinnamic acid, soluble sugars, fatty acids and carotenoids, and secondary substances such as glucosinolates that are currently recognized by the antioxidant and anti-carcinogenic effects. The diamondback moth, Plutella xylostella, is one of the main limiting factors of this crop in the world, due to the serious damage that cause to plants, depreciating the product and causing serious reductions in the field production. The knowledge of the biology of this insect in different cultivars is important so that you can determine those less favorable to the pest development and reproduce. In this context, the objective of this study was to evaluate the influence of the larvae food substrate (Brassicaceae’s varieties) in the P. xylostella development over 18 generations. Insects were reared on 3 comercial varieties/cultivars of importance to the northeastern of Sao Paulo State: Brassica oleracea var. acephala - kale Manteiga hibrida HS-20, Brassica oleracea var. italica - broccoli Piracicaba and Brassica oleracea var. capitata - cabbage Bob Cat. Every 3 generations the biological aspects of P. xylostella were evaluated in laboratory trials. The biological parameters evaluated were: leaf consumption, larval period, larval viability, pupal period, pupal viability, pupal weight, sex ratio, number of eggs per female, egg fertility, and longevity of males and females. The results were analysed comparing generations and cultivars. The biological parameters of P. xylostella showed that cabbage cultivar was less consumed and the larval period was longer while the pupal period was shorter. However, the low initial performance of this cultivar was being improved over the generations, matching the others in the latest generations ...

Espécies da família Brassicaceae fazem parte da alimentação básica mundial. Suas características nutricionais mostram altos teores de vitaminas, fibras, minerais, fenóis, flavonóides, ácido hidroxicinâmico, açúcares solúveis, ácidos graxos e carotenoides, além de substâncias secundárias como glucosinolatos que, atualmente, são reconhecidos pelas propriedades antioxidantes e anticancerígenas. A traça-das-crucíferas, Plutella xylostella, é um dos principais fatores limitantes deste cultivo no mundo, devido aos sérios danos que causa às plantas, depreciando o produto e ocasionando grandes perdas nos campos de produção, portanto, o conhecimento do desenvolvimento deste inseto em diferentes cultivares é importante para que se possa determinar aquelas menos propícias para o inseto. Neste contexto, o objetivo deste trabalho foi verificar se houve influência do substrato alimentar das lagartas (variedades de Brassicaceae) no desenvolvimento de P. xylostella, ao longo de 18 gerações. Os insetos foram criados em 3 variedades/cultivares de importância comercial para a região nordeste do Estado de São Paulo: Brassica oleracea var. acephala - couve Manteiga hibrida HS-20, Brassica oleracea var. italica - brócolis Piracicaba e Brassica oleracea var. capitata - repolho Bob Cat. A cada 3 gerações aspectos biológicos do inseto criado nos diferentes substratos de alimentação foram avaliados em ensaios de laboratório. As características biológicas analisadas foram: consumo foliar, período larval, viabilidade de larvas, período pupal, viabilidade de pupas, peso pupal, razão sexual, número de ovos por fêmea, fertilidade de ovos, longevidade de machos e longevidade de fêmeas. Os resultados foram submetidos a análise fatorial comparando-se gerações e cultivares. Os parâmetros biológicos de P. xylostella demonstraram que repolho foi o menos consumido e o que apresentou ...
Keywords: Traça; Inseto; Pragas agricolas; Lepidoptero; Substratos; Insects